OPTIMALISASI RANCANGAN JARINGAN KOMPUTER MENGGUNAKAN GOOGLE SKETCHUP - Taufik Ardiantoro; Joko Triyono; Erfanti Fatkhiyah (Jurnal Jarkom, 2016)
All the time, mapping of computer networks in a building is a visualization in the form of 2-dimensional. To increase the quality of mapping network computer then can be made in the form of visualization mapping that resembles to the real life. It use the form of 3-dimensional (3D).The scope of the problem in this research there are a few limitation such as data collection and the creation of 3D computer network on campus 3 IST AKPRIND Yogyakarta. Objects that are examined include lecture rooms, laboratories, faculty room, and another room in campus 3 of IST AKPRIND Yogyakarta. The process of creating 3D computer network uses software google sketchUp. The data used in the form of survey results of observations of some parts of the building and photographs of every room. Network mapping results in the form of 3D is an interesting media, easily understood by users, can be used as a reference for the maintenance and development of the network, it can even be used as a means of introduction to campus building 3 description thoroughly. 3D image of computer networks and the building of the campus 3 IST AKPRIND produces up to date information about the physical building at this time.